Systematic assessment of nymphs of Diesingiinae (Pentastomida: Sebekidae) parasitizing Palloceros harpagos (Cyprinodontiformes: Poeciliidae) from Parque Nacional Iguazú, Argentina: Filling gaps in an incomplete phylogenetic framework - Montes, Martin Miguel (2023)
During a search for parasites in fishes from Iguazu River, Argentina, a nymph of pentastomid was found encysted on mesenteries of Phalloceros harpagos. The 28S rDNA and COI mt-DNA were used to compare with the sequences deposited in the GenBank. Pentastomid nymphs belong to the subfamily Diesingiinae (Sebekidae) for having chloride cell pores distributed in a single row per annulus; also, the hooks and rows of spines of our material differ to other genera. Present specimens are most likely Diesingia sp., having 63-74 annuli, a U shaped oral cadre with fibers closing anteriorly and a peg like extension of the oral cadre. The 28S rDNA analysis places our samples into a sister group of Alofia sp., but the COI mt-DNA situate them on the base of the clade. In conclusion, our pentastomid positively belongs to Diesingia sp., however, indisputable assignation requires a reliable description of the nymph, or the availability of sequences linking nymphs and adults, which even could provide evidence of a new hitherto undescribed genus. Aditionally, the systematic position of Sebekia oxycephala previously described by P. harpagos is discussed on the basis of our results, allowing us to suggest a re-assignation of such specimens to the genus Diesingia.